Generation Z and the Search for Religious Knowledge on Social Media - Romario (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article examines senior high school students in their search for Islamic knowledge. This study uses ethnographic methods and life stories which were carried out intensively for three months. Data was collected by interviewing eighteen students from three schools, namely MAN 1 Yogyakarta, SMA Negeri 8 Yogyakarta, and SMA Muhammadiyah 1 Yogyakarta. I took six informants from each school consisting of three students and three female students. In addition, I also made observations in observing clerics and religious content accessed by informants on social media. This article shows that high school students who are referred to as generation Z. Seek religious knowledge not only through extracurricular activities such as Rohis, but also through social media. Generation Z's consumption of religious knowledge on social media cannot be separated from the long process of Islamizing public space in Indonesia. The Islamization of thispublic space affects the social media space so that it gives birth to a lot of religious content and popular clerics from various different backgrounds that are liked by young people. This study demonstrates two models of consumption of religious knowledge of generation Z. First, generation Z who access religious knowledge from various ustaz backgrounds. Second, Generation Z is consistent in accessing religious knowledge on social media based on similar backgrounds, affiliations or religious organizations. This research contributes to the study of changes and developments of high school students in seeking religious knowledge.